The functions of teachers' code switching in multilingual and multicultural high school classrooms in the Siyanda District of the Northern Cape Province - Uys, Dawid (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2010.